2022
DOI: 10.3390/molecules27020574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Total Phenolic and Flavonoid Contents, Antibacterial and Antibiofilm Activities of Hungarian Propolis Ethanolic Extract against Staphylococcus aureus

Abstract: Propolis is a natural bee product that is widely used in folk medicine. This study aimed to evaluate the antimicrobial and antibiofilm activities of ethanolic extract of propolis (EEP) on methicillin-resistant and sensitive Staphylococcus aureus (MRSA and MSSA). Propolis samples were collected from six regions in Hungary. The minimum inhibitory concentrations (MIC) values and the interaction of EEP-antibiotics were evaluated by the broth microdilution and the chequerboard broth microdilution methods, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 73 publications
1
11
0
2
Order By: Relevance
“…The EEP in combination with vancomycin synergistically showed effective inhibition and degradation against biofilm formation and maturation, respectively. The EEP at a concentration of 200 μg/mL against MSSA and MRSA showed 47–87% biofilm degradation, respectively [ 188 ]. Alandejani et al have determined the antibiofilm activity of four different kinds of honey: Manuka honey (from New Zealand), Buckwheat and Canadian clover honey (from Canada), and Sidr honey (from Yemen).…”
Section: Biofilm Controlling Compoundsmentioning
confidence: 99%
“…The EEP in combination with vancomycin synergistically showed effective inhibition and degradation against biofilm formation and maturation, respectively. The EEP at a concentration of 200 μg/mL against MSSA and MRSA showed 47–87% biofilm degradation, respectively [ 188 ]. Alandejani et al have determined the antibiofilm activity of four different kinds of honey: Manuka honey (from New Zealand), Buckwheat and Canadian clover honey (from Canada), and Sidr honey (from Yemen).…”
Section: Biofilm Controlling Compoundsmentioning
confidence: 99%
“…The up-bound capacity of the EtOAc fraction may be due to the presence of a higher quantity of flavonoids and other major volatile bioactive compounds. In extended studies, the compounds (i.e., flavonoids, coumarins, and essential oil) were reported to possess positive effects on human health, e.g., antibacterial, antioxidant, anti-diabetes, anti-inflammatory, and anti-allergic activities (Bouchelaghem et al 2022 ; Xiao 2022 ; Gulcin et al 2022 ). Oxidative stress resulting in the formation of free radicals was proved as a major factor in disease development and complications of diabetes (Tripathi and Chandra 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…The HPLC analysis showed that the flavonoid, phenolic acid, and other compounds of crude Romanian propolis and their ethanolic extract are similar to other ethanolic extracts of propolis, mainly of European origin [15,18,[30][31][32][33].…”
Section: Ethanolic Extract Of Romanian Propolis Analysesmentioning
confidence: 90%